Sensory and Physical Characteristics of Mackerel Fish Galantine (Rastelliger kanagurta) With Straw Mushroom (Volvariella volvacea) Subtitution - Isna Fitriah; Diah Ayu Puspasari; Andra Tersiana Wati (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
Vegetarian food highly favored as part today’s healthy lifestyle trend. Straw mushrooms one type edible mushroom that still rarely utilized, so innovation in developing mackerel galantine with straw mushrooms can enhance the potential both ingredients. This study aims to determine the panelists’ preference levels and physical characteristics galantine with different ratios of mackerel and straw mushrooms. A 2-factorial Complete Random Design (RAL) with a non-factorial arrangement and ratios of mackerel to straw mushroom in galantine G1(100:0); G2(75:25); G3(25:75); G4(0:100) sensory analysis and physical tests color and texture were conducted. Data were analyzed using ANOVA, and if significant differences found, further analysis was using the DMRT test. The results showed that panelists preferred the color of G2 with average score of 3.68, aroma of G3 with 3.48, taste of G2 and G3 with 3.3, texture of G1 with 3.26, and overall preference for G2 with 3.56. Physical color testing showed a L* value of 41.25; a* value of 1.21; and b* value of 12.4; texture test indicated that the hardest texture was found in G3 with a value of 126.26. Based on the results, the ratio of mackerel and straw mushrooms significantly affected the sensory and physical characteristics of the galantine. Keywords: Fish, Galantine, Mushroom, Physical, Sensory